Assessment of carotid arteries in stroke patients by ultrasonography and color Doppler - Saifi, Shenaz G. A.; Rustagi, Vikash; Shetty, Dev (International Journal of Advances in Medicine, 2022)
Background: Prevalence and associated mortality and morbidity rates apprehend stroke as a major health concern worldwide. Atherosclerotic disease of carotid arteries is the most common source of stroke. Quick and effective diagnosis, management and treatment of stroke is essential. Conventional diagnostic imaging techniques lacks the efficacy to rapidly and accurately dragonize stroke. Current investigation is focused towards assessing carotid arteries in stroke patients by ultrasonography and color Doppler to study the locate and study the morphology of lesion in carotid artery and to grade severity and extent of stenosis. Methods: A prospective observational study was performed on stroke patients of more than 40 years of age. The study was conducted at the department of radio diagnosis in a tertiary care center for a period of 18 months. Varied color Doppler parameters were studied and optimized to assess the morphology and surface of plaques and to determine stenosis Results: Mean age of the patients with carotid lesion was observed to be 59.7±9.8 years and male patients outnumbered postmenopausal female patients. Hemiparesis was the most common clinical presentation. Majority of patients exhibited raised intimomedial thickness and single or multiple plaques commonly in carotid bulb. Plaques of type II with irregular surface were most commonly observed which exhibited mostly 50-69% stenosis. Conclusions: The carotid artery embolic occlusion stenosis is the primary cause of stroke. Doppler sonography provides a rapid, noninvasive, relatively inexpensive and accurate means of diagnosing carotid stenosis, to determine the degree of cervical carotid stenosis and plaque morphology.